'I will never ever go back': patients' written narratives of health care communication. Issue 7 (6th June 2018) - Denniston, Charlotte; Molloy, Elizabeth; Rees, Charlotte E
Abstract : Context: Although communication with patients is essential to health care, education designed to develop patient‐centred communication often ignores patients' voices. Patient stories may offer a means to explore patient experiences to inform patient‐centred communication skills education design. Objectives: Our research questions were: (i) What are the features of patients' health care communication narratives? (ii) What differences exist between patient narratives evaluated as positive and those evaluated as negative? (iii) How do patients narrate emotion in their narratives? Methods: This interpretivist research was underpinned by social constructionism. We employed a narrative approach to design an online questionnaire that was advertised to patients in the community. Analysis of the stories that were generated involved analysis of what was written (i.e. framework analysis) and of how it was written (i.e. attending to linguistic features). Results: Participants shared 180 written narratives about previous health care professional (HCP) communication interactions. Narratives commonly included those of female patients seeking help for musculoskeletal or psychological concerns, which most frequently had occurred within the previous 6 months with male general practitioners in community settings. Framework analysis revealed four key themes: (i) patient actions during consultations; (ii) patient actions afterwards; (iii) lasting legacy, and (iv) interpersonal factors. Patients in narratives evaluated as positive actively engaged during and after interactions, had ongoing positive relationships with HCPs and felt valued in these relationships. Patients in narratives evaluated as negative were either passive or active during the interaction, but mostly failed to return to the HCP and felt devalued in their interaction. Further analysis of the linguistic features of select narratives revealed rich constructions of positive and negative emotions emphasising the lasting legacies of these interactions. Conclusions: Analysis of patient narratives provides a detailed way of exploring patients' experiences, emotions and behaviours during and after consultations. Educational implications include emphasising the importance of valuing the patient, and of seeking and acting on patient feedback to calibrate HCPs' patient‐centred communication practices. Abstract : The authors explore patients' stories of health care communication to better inform patient‐centred care curriculum design.